Production of biodiesel from waste cooking oil via ultrasonic-assisted catalytic system - Ngadi, Norzita (2015)
In this study, production of biodiesel from waste cooking oil (WCO) was carried out via ultrasonic-assisted transesterification method. Calcium oxide (CaO) was used as a catalyst. The effects of methanol to oil molar ratio, reaction temperature and the catalyst amount towards the percentage conversion of oil to biodiesel were investigated. The biodiesel produced was analyzed using GC-FID method. The results obtained showed that 82 % of oil was successfully converted into biodiesel. This indicates that the used oil (WCO) has the potential to be the future source of biodiesel. Catalyst concentration of 3 w/w%, methanol to oil molar ratio of 15:1 and temperature of 65°C are the best condition for the conversion of oil to biodiesel. The result obtained was found out that, methanol to oil molar ratio and catalyst amount has given significant effect on the conversion of oil. However, temperature ranged from (35 to 75) °C apparently, showed no significant effect on percentage conversion of oil.